EFFECTIVENESS OF DIGITAL MARKETING TO INCREASE PURCHASE INTEREST OF CIREBON CITY CAFE VISITORS - Ananda Gresycia Wulandari; Fadilla Harningtias; Siska Ernawati Fatimah (International Journal of Innovative Technologies in Social Science, 2024)
This study is intended to determine the influence of Digital Marketing through Store Atmosphere on the buying interest of Café visitors in the city of Cirebon. The population used in this study was café visitors in the city of Cirebon. The sampling technique uses Incidental Sampling. In testing this data using analysis with Structural Equation Modeling- Partial Least Square (SEM-PLS), with respondents amounting to 200. The results show that Buying Interest is partially positive and significant which is influenced by 17% Digital Marketing and Store Atmosphere partially affects Buying Interest by 81%. This proves that Buying Interest is a link between the Digital Marketing variable and the Digital Marketing variable. This research provides theoretical implications for references for future research related to Digital Marketing, Store Atmosphere and Buying Interest, especially in Cafes. The implication is in the form of Café suggestions so that in the future it can improve the quality of Digital Marketing and also Store Atmosphere for Purchase Interest to increase.